Konsep Penebusan Kosmik Dalam Mitologi Tradisi Pante pada Masyarakat Manggarai Indonesia - Sefrianus Juhani; Raymundus I Made Sudhiarsa; Alexander Jebadu; Bernadus Raho; Jόzef Trzebuniak (Center for Research and Development of Religious Literature and Heritage, 2023)
This study aims to explore the cosmic redemption concepts in the mythology of the pante tradition in Manggarai community. Pante tradition was an attempt to promote an attitude of respect for non-human creations so that nature would return to its harmonious state. The data was obtained through interviews with several key informants who were very close to these myths, including some palm tappers from several villages in Manggarai. From interviews and collected documents, several myths were found in the pante tradition. In Manggarai mythology, it is believed that there is inseparable relationship between humans, non-human creations, and the Supreme Being. Each creation has a contribution to the survival of the others and has eschatological future. The Manggarai people also believe that there is a place for the eternal life called pa'ang be le. This finding contributes to the development of ecological theology in the Indonesian Catholic Church and the universal Church. In addition, the awareness of the ultimate future for all creation strengthens the commitment of the Christians to preserve the environment.